THE EFFECT OF EMPLOYEE INTEGRITY, COORDINATION, FACILITIES AND INFRASTRUCTURE ON EMPLOYEE PERFORMANCE IN TANDES DISTRICT SURABAYA CITY: PENGARUH INTEGRITAS PEGAWAI, KOORDINASI DAN SARANA PRASARANA TERHADAP KINERJA PEGAWAI KECAMATAN TANDES KOTA SURABAYA - Siti Julaikah; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Humans as a very potential resource with their abilities and skills can drive the wheels of the institution. This makes human resources the most important asset of the institution in determining the realization of the company's goals. The success of an organization is greatly influenced by the performance of its individual employees. Every organization or company will always try to improve the performance of its employees, with the hope that what the company's goals will be achieved. Research on employee performance can be influenced by several factors, one of which is integrity, coordination, infrastructure. In this study, a quantitative approach was taken in analyzing the problem. The purpose of this study was to test the effect of employee integrity, coordination and infrastructure on employee performance. Where this study consists of 3 independent variables, namely employee integrity, coordination, infrastructure and the dependent variable is employee performance. The study was conducted in Tandes District using a saturated sampling technique with 69 respondents. Data collection techniques were carried out by distributing questionnaires and Likert scale assessments. The analysis was carried out using the product moment correlation test tool and multiple correlation with SPSS software. The results obtained in this study are: (1) Integrity has a significant influence on employee performance (2) Coordination has a significant influence on employee performance (3) Facilities and infrastructure have a significant influence on employee performance